2020
DOI: 10.1177/2192568220935107
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Proximal Junctional Kyphosis With Pedicle Screws at Upper Instrumented Vertebrae in Posterior Spinal Fusion for Adolescent Idiopathic Scoliosis

Abstract: Study Design: Longitudinal cohort. Objectives: Posterior spinal fusion (PSF) using all-pedicle screw constructs has become the standard procedure in the treatment of adolescent idiopathic scoliosis (AIS). However, there have been several reports that all-pedicle screw constructs or the use of pedicle screws at the upper instrumented vertebrae (UIV) increases the incidence of proximal junctional kyphosis (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…The extended fusion group also had higher risk of PJK in this study. This may partially explain the higher incidence rate of PJK in the present study rather than the one in previous studies after selective TL/L fusion of Lenke 5C patients [ 3 , 4 , 23 ]. Hence, extended fusion should be carefully evaluated in patients with Lenke 5C AIS who have a TIA of > 71°.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…The extended fusion group also had higher risk of PJK in this study. This may partially explain the higher incidence rate of PJK in the present study rather than the one in previous studies after selective TL/L fusion of Lenke 5C patients [ 3 , 4 , 23 ]. Hence, extended fusion should be carefully evaluated in patients with Lenke 5C AIS who have a TIA of > 71°.…”
Section: Discussioncontrasting
confidence: 67%
“…These patients may have developed an immediate increase in TK after surgery, but the large TIA also meant that they needed a much larger GTK at the final follow-up. In Ogura’s study, the increased TK at final follow-up time was also risk factor of PJK [ 23 ]. The increasing TK and GTK immediately after surgery were not enough for these patients; the TK and GTK continued to increase during follow-up, leading to PJK at the final follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 22 studies were analyzed in our meta-analysis. In our systematic review, we included a total of 3922 patients; all were under the age of 18 years and were operated on due to adolescent idiopathic scoliosis [1,4,5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (Figure 1). statistical heterogeneity (α = 0.05), the χ 2 test was employed, and I 2 statistics were used to quantitatively assess heterogeneity.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…It can provide a stronger control force and reduce the mechanical stress of the instrumentation. However, dual growing rods and pedicle screw fixation, the most stable and effective option, may be more likely to lead to PJK (Pan et al, 2018;Ogura et al, 2021). Clinical studies have shown that there are many factors associated with PJK, but the relationship between the position of pedicle screw fixation and PJK is still a controversial topic (Homans et al, 2020).…”
Section: Discussionmentioning
confidence: 99%